TRANSPOR IODIN MELALUI MEMBRAN KLOROFORM DENGAN TENIK MEMBRAN CAIR FASA RUAH - Refinel -; Zaharasmi Kahar; Sukmawita - (Jurnal Riset Kimia, 2011)
Vol 5 No 1ABSTRACT The transport of iodine through a bulk liquid membrane containing chloroform as the solvent and alkaline sodium sulfite solution as the receiving phase was studied .Iodine transport was performed by bulk liquid membrane technique consist of 10 mL I2/KI solution as feed phase, Na2SO3 (20 mL) and NaOH solution as receiving phase, and chloroform (30 mL) as membrane phase which was stirred 100 rpm. The presence of iodine both in feed and receiving phase then where determined by Spectrophotometer UV-Vis with λ max at 567 nm. The optimum conditions for iodine transport investigated from this work are 4x10-3 N, pH 4 in feed phase, pH 9 in receiving phase, I2 : KI ratio in feed phase (2 : 5), and a stirring duration is 180 minutes. As conclusion the bulk liquid membrane technique with Na2SO3 and NaOH as receiving and acception substances is potential for iodine transport resulting 78.6 % of iodin transport. Keywords: Iodine, transport, chloroform, bulk liquid membrane, Na2SO3, NaOH